Differences in the patient's and the physician's perspective of disease in psoriatic arthritis - Dandorfer, Stefan; Rech, Jürgen; Manger, Bernhard; Schett, Georg; Englbrecht, Matthias (Seminars in Arthritis and Rheumatism, 2012)
Objective: To define the relative impact of disease components of psoriatic arthritis (PsA) on the global burden of disease and to compare physician's and patients' ratings of disease activity. Methods: PsA patients fulfilling the Classification Criteria for Psoriatic Arthritis (N = 55) were asked for an evaluation of the absolute and relative impact of general and specific rheumatic symptoms (ie, arthritis, enthesitis, spinal disease, dactylitis), general and specific psoriatic symptoms (skin disease, nail disease), and other common symptoms (eg, fatigue). Results were related to the respective physician's evaluations of disease-related symptoms based on visual analog scale (VAS) ratings and comparative measures of disease activity (ie, swollen and tender joint counts, MASES, PASI, NAPSI). Results: One-half of the global burden of disease in PsA patients was attributed to rheumatic symptoms with peripheral arthritis as the leading component, whereas the other one-half was equally distributed to psoriatic and additional common symptoms such as fatigue. In general, corresponding patient and physician ratings of global, rheumatic, and psoriatic disease activity showed good correlations when using VAS but at the same time revealed significantly lower ratings of the corresponding physician on VAS and transformed comparative measures (all P ≤ 0.02). Conclusions: Although we found good correlations of various disease activity measures, physicians usually evaluated the disease activity of PsA lower than patients. These results highlight the necessity of incorporating patient reported outcome measures into the assessment of disease activity in PsA, which can easily be visualized with the help of a spiderweb graph. © 2012 Elsevier Inc.
CRIS-Team Scopus Importer:2021-02-03
Keywords: Disease activity; Patient reported outcomes; Psoriatic arthritis